Efektivitas Isbat Nikah Keliling terhadap Aksesibilitas Bagi Masyarakat Kabupaten Polewali Mandar: Analisis Maslahah Mursalah - Aziz, Sherina Mutiara Puteri; Akbar, Alif; Idrus, Achmad Musyahid (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The phenomenon that occurs in the people of Tinambung District, Polewali Mandar Regency is that people do not have marriage books because they are still underage so their marriages cannot be registered. If marriage registration is not carried out, it will lead to irregularities in people's lives which will lead to legal smuggling. To get a marriage book, the couple must attend the marriage isbat at the Polewali Mandar Religious Court Office. However, the people of Tinambung District find it difficult to apply for marriage isbat because the distance to the Polewali Mandar Religious Court is quite far, transportation costs are expensive, and they are old. Starting from this problem, the Polewali Mandar Religious Court, in collaboration with the Polewali Religious Office, held a mobile marriage isbat program so that people could get marriage certificates. This research is included in field research (qualitative) which uses the Normative Syar'i Approach which refers to approaching problems from the perspective of Islamic law. From the results of research conducted by researchers regarding mobile marriage isbat, it was concluded that mobile marriage isbat in Tinambung District is very effective in increasing accessibility and if viewed from a maslahah perspective, mobile marriage isbat can be categorized as maslahah murlah. Because marriage isbat has many benefits compared to its harms, one of which is in terms of protecting offspring. With the marriage isbat, children born out of wedlock will receive a birth certificate which can be used to register for school. Not only will the couple benefit, but the offspring born from the marriage will also benefit if both parents follow the marriage isbat.